Effect of the topology on the antibacterial activity of cationic polythioether synthesized by all‐click chemistry. Issue 12 (22nd May 2020) - Zheng, Yaochen; Liu, Jian; Guo, Yan; Zhang, Qian; Gao, Xuan; Gao, Zhengguo; He, Tao; Ban, Qingfu
Abstract: Cationic compounds often serve as antibacterial materials for a wide range of applications. However, the relationship of topology−antibacterial activity has been rarely revealed. Herein, three cationic polythioethers (CPTEs) with hyperbranched topologies are well designed and facilely synthesized via an all‐click chemistry strategy (including thiol‐ene and epoxy‐amine additions). These as‐prepared CPTEs were found to exhibited outstanding antibacterial activity against Escherichia coli and Staphylococcus aureus with minimum inhibitory concentrations against E. coli of 7.3, 14.6, and 14.6 μg ml −1, and against S. aureus of 14.6, 29.2, and 29.2 μg ml −1, respectively. The antibacterial activity is coincident with their degree of branching (DB, their DB values of 0.81, 0.48, and 0.27), which is mainly attributed to the inherent three‐dimensional structure. The present strategy reveals the relationship of polymer topology and antibacterial activity, providing a novel possibility for designing and/or synthesis of high‐efficiency antibacterial agents. Abstract : In this study, three cationic polythioethers (CPTEs) with hyperbranched topologies were synthesized via click chemistry. The obtained CPTEs exhibit outstanding antibacterial activity against Escherichia coli and Staphylococcus aureus with minimum inhibitory concentrations. The results demonstrate the relationship between polymer topology and antibacterial activity. It also provides a potential pathway to design antibacterial agents with high efficiency.